2017
DOI: 10.1007/s10517-017-3791-1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Progressive Heart Failure on Cerebral Hemodynamics and Monoamine Metabolism in CNS

Abstract: Compensated and decompensated heart failure are characterized by different associations of disorders in the brain and heart. In compensated heart failure, the blood flow in the common carotid and basilar arteries does not change. Exacerbation of heart failure leads to severe decompensation and is accompanied by a decrease in blood flow in the carotid and basilar arteries. Changes in monoamine content occurring in the brain at different stages of heart failure are determined by various factors. The functional e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…For instance, in a longitudinal animal study, induction of cerebral ischemia in rats led to reduced striatal 11 C‐raclopride binding over time . Another study showed that heart failure was followed by attenuated cerebral blood flow as well as DA levels …”
Section: Discussionmentioning
confidence: 99%
“…For instance, in a longitudinal animal study, induction of cerebral ischemia in rats led to reduced striatal 11 C‐raclopride binding over time . Another study showed that heart failure was followed by attenuated cerebral blood flow as well as DA levels …”
Section: Discussionmentioning
confidence: 99%
“…Two major pathological factors have been proposed to contribute to neurological dysfunction in HF, including end-organ hypoperfusion/hypoxia [14][15][16][17][18] a state associated also to cognitive impairment and neurodegeneration such as Alzheimer. 19 Additionally, recent studies support neuroinflammation as a common finding in numerous brain regions during HF.…”
mentioning
confidence: 99%
“…altered cerebral hemodynamics in heart failure. Reduced cerebral blood flow velocity and regional cerebral oxygen saturation was observed in HF patients (Mamalyga andMamalyga, 2017, Erkelens et al, 2017).…”
Section: Introductionmentioning
confidence: 98%